Combined Novel Microfocused Ultrasound and Microneedle Fractional Radiofrequency System for Multilayered Facial Rejuvenation: A Prospective, Randomized, and Split‐Face Study - Wang, Ruiyao; Peng, Guangling; Chen, Yangmei; Shao, Xinyi; Liu, Lin; Chen, Tingqiao; Shi, Mengcen; Zhong, Judan; Ou, Yi; Chen, Jin (Journal of cosmetic dermatology, 2025)
ABSTRACT Background With the aging population, the demand for skin anti‐aging treatments has been steadily rising, prompting the development of advanced non‐invasive therapies. Aims To evaluate the efficacy and safety of microfocused ultrasound (MFU) combined with microneedle fractional radiofrequency (MFR) for facial rejuvenation. Methods This study involved 26 patients experiencing facial laxity. Each patient received one full‐face MFU treatment and one MFR treatment on one side of the face, which was randomly assigned. All treatments were performed on the same day. Facial photoaging parameters were assessed using VISIA, skin fat thickness changes were measured via ultrasound, and subjective evaluations were recorded at Months 0, 1, and 3. Side effects were recorded during treatments and each follow‐up visit. Results The VISIA analysis demonstrated notable enhancements in skin texture, wrinkles, pores, spots, and red areas on the combined treatment side. Ultrasound examinations revealed a significant reduction in subcutaneous fat thickness, particularly at the masseter and the middle of the cheek on the combined side. The study showed improvements in the Global Aesthetic Improvement Scale (GAIS) and Wrinkle Severity Rating Scale (WSRS) scores, with the combined treatment side outperforming the control side at the 3 month mark. Over 90% of participants expressed satisfaction with the treatment outcomes. Mild side effects, such as erythema, purpura, and edema, were observed but resolved without special interventions. Conclusions The combination of MFU and MFR for facial rejuvenation is both safe and effective. The combined treatment demonstrates superior enhancement in skin tightening, depigmentation, and pore refinement within a single therapeutic session.